Linear Mixed Model for Oil Palm Parents Selection - Sonhaji, Abdullah; Pasaribu, Udjianna Sekteria; Indratno, Sapto Wahyu; Pancoro, Adi (Communication in Biomathematical Sciences, 2025)
The objective of plant breeding is to obtain superior seeds. These seeds originated from parents that can pass their superior traits to their progeny. The observed characteristics of the progeny (phenotype) determined the traits of these seeds. Therefore, we performed a progeny analysis. In this analysis, the data samples were collected from Riau in Sumatera and Kumai in Kalimantan (two locations). The main objective is to find superior parents from these two locations. The superiority of the selected parents lies not only in passing high production traits but also in adaptability (fit) to the diversity or variability of the environment or locations. This analysis calculates the General Combining Ability (GCA) values for both male and female parents using the Linear Mixed Model (LMM). The experimental design, as the source of data, was an alpha lattice design, so the LMM contains locations, replicas, blocks, male and female parents, and the progeny factors. The analyzed phenotype is Fresh Fruit Bunches of third-year production. Since the data sets of the two locations were nonintersect, the model uses the coefficient of parentage (additive relationship matrix) to link both. The results of the GCA analysis showed that selected female parents were 137, 155, 126, 147, and 159 (Dura), and 101, 113, 109, and 117 for male parents. They are among the parents with highly productive progenies. There are also new potential crossings not currently available on the plantation - for example, the crossing 137 x 101 with the additive genetic value of 35.37.